Les enjeux de la fondation d’une science économique dite islamique - Frédéric Coste (Université de Provence, 2018)
After the 1970s, some political-religious activists aim at founding scientifically an economic discipline in compliance with what would be the homo islamicus. They assert to contradict some core assumptions of orthodox Economics, and to propose a moral framework supposed to stem from shariah. This ‘‘Islamic Economics’’ purports to create an interest-free economic system, based also on a redistributive principle. This normative approach claiming to be scientific finds its origins in political islam struggles in the 1940s against communism and capitalism.